An integrated framework for knowledge audit and capture - Ahmad, Mohd Sharifuddin; Mohd Yusof, Mohd Zaliman; Ahmad, Azhana (2010)
In this paper, an integrated framework for knowledge audit and capture using the task analysis approach is presented.We first identify the types of knowledge that could be ascribed to tasks and analyze a task by breaking it down into subtasks and task elements. We then identify the skills and knowledge required to perform the tasks at this level.The framework is validated and tested on an expertise-based task, the findings of which are compiled as a knowledge-based document.